Biodiversity conservation strategy in Malaysia: from an Islamic perspective - Mohd. Azlan J. Abdul Gulam Azad, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
The rapid decline of world’s biodiversity and increasing need of natural resources to accommodate the growing population suggest that the current western philosophy of conservation biology is not achieving its mission and objective as expected in Southeast Asia. The existing religious tools and channels for conservation should be seriously considered. There is a high potential in achieving high standards of conservation biology if management of natural resources adheres to the fundamental principles of Islam in Malaysia. However religious approaches are mainly limited to Islamic norms and treated independently in many parts of Southeast Asia, including Malaysia. Therefore there is an urgent need to synergize Islamic concepts in conservation biology with the existing governance system. It is believed if Islamic concepts are genuinely practised and amalgamated into the existing implementation and governance structure in conservation biology, the future for biodiversity in this region will be bright.